Program Potensi Desa dan Penerapan Sistem Budidaya Mina Padi Desa Tamanan, Kapanewon Banguntapan, Kabupaten Bantul - Kurnianingtyas, Chandra Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
KKN 80 Atma Jaya University Yogyakarta chose Bantul and Kulon Progo Regencies as locations to implement the Community 5.0 Community Service Program. The author found the location of KKN in Tamanan Village. Tamanan Village is one of the villages located in Banguntapan District, Bantul Regency, Yogyakarta Special Region. This KKN 80 activity aims to help the residents of Tamanan Village explore and look for village potentials that can be developed in order to provide added value to the village. The potential of the village owned can be in the form of natural resources, agricultural or plantation land, natural or artificial tourism as well as various sources that can be utilized for the progress and development of the village. The service method used is counseling, the author also seeks information related to the village's potential. The author plans to make innovations regarding the application of the Mina Padi cultivation system because in Tamana Village there is potential for rice fields that can apply the system. The results of mina padi are rice and fish. The extension stage of the Mina Padi system will be documented in the form of an interactive e-book and video, in order to make it easier for the residents of Tamanan Village to realize it and it is hoped that it will produce an abundant variety of harvest types, as well as increase the income of the residents of Tamanan Village.